2010
DOI: 10.3184/146867810x12686717520194
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin-Surfactant Mixed Systems as Reaction Media

Abstract: In recent years our reseach group has investigated the chemical behaviour of β-cyclodextrin (CD)/surfactant mixed systems and their characteristics as reaction media. The results have been interpreted in terms of a pseudophase model that takes into account the formation of both CD-surfactant and CD-substrate complexes and also, in some cases, the exchange of X- and OH- ions between the micellar and aqueous pseudophases. from the experimental results it was concluded that the presence of CD has no effect on exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 74 publications
1
6
0
Order By: Relevance
“…Because this SPFO:OTEAB composition ratio was not very far from 1:1, although the cmc*'s were obviously increased [(2.46 and 2.43) mmol·kg −1 , respectively] in comparison with the cmc of equimolar OTEAB/SPFO (1.64 mmol·kg −1 ), the total concentrations of surfactant monomers [(1.94 and 1.61) mmol·kg −1 , respectively] were close to the cmc of equimolar OTEAB/SPFO. It was also consistent with the general situation that the presence of CD has no effect on existing strong micelles but raises the cmc …”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Because this SPFO:OTEAB composition ratio was not very far from 1:1, although the cmc*'s were obviously increased [(2.46 and 2.43) mmol·kg −1 , respectively] in comparison with the cmc of equimolar OTEAB/SPFO (1.64 mmol·kg −1 ), the total concentrations of surfactant monomers [(1.94 and 1.61) mmol·kg −1 , respectively] were close to the cmc of equimolar OTEAB/SPFO. It was also consistent with the general situation that the presence of CD has no effect on existing strong micelles but raises the cmc …”
Section: Discussionsupporting
confidence: 89%
“…Although CD (free and complexed) might show affinity toward the micelles because of ion−dipole interactions between the carboxylate headgroups in the hydrophilic shell and the hydroxyl groups of the CD, ,, this kind of interaction between CD and micelles might be weak because the cationic−anionic surfactant headgroups in micelles strongly interact with each other. Generally it is concluded that the presence of CD has no effect on existing strong micelles but increases the cmc . Here, with the assumptions that α-CD included only surfactant monomers in solution and that the complexes did not participate in the micelles, the concentrations of SPFO and OTEAB in Table could be regarded as the critical composition of micelles: the sums of C SPFO and C OTEAB were 1.94 mmol·kg −1 (critical composition of micelles SPFO:OTEAB = 2.95) and 1.61 mmol·kg −1 (critical composition of micelles SPFO:OTEAB = 1.60) for systems 1 and 2, respectively, which was consistent with the discussion in our previous work that SPFO might be the much more contributive component in mixed OTEAB/SPFO micelles .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pseudophase model applied to micelles has also been satisfactory for the analysis of the kinetic results in more complex micellar systems such as mixed micellar-cyclodextrin systems [31][32][33][34][35][36][37] or pseudo-micellar humic acids aggregates [38][39][40][41][42].…”
Section: The Pseudophase Modelmentioning
confidence: 99%